2020
DOI: 10.1088/1742-6596/1431/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Study of the high-velocity impact of tungsten particles with a steel target

Abstract: The high-velocity impact of a tungsten particle flux with the surface layer of steel (U8) samples is studied. High-speed photography which was used to record the motion of tungsten particles and detonation products shows that tungsten particles move with an average velocity of 2.4 km/s. Microstructure studies have revealed that upon the impact of tungsten particles with the surface of the target, the temperature in the active zone exceeds the temperature of the peritectoid reaction in the Fe-W system, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…The change in mechanical properties under dynamic alloying [ 35 , 41 , 42 , 43 ] indirectly points to a change in the material’s physical properties, and the peculiarities of the dynamic alloying process in the SDP mode should increase the anisotropy of the material being processed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in mechanical properties under dynamic alloying [ 35 , 41 , 42 , 43 ] indirectly points to a change in the material’s physical properties, and the peculiarities of the dynamic alloying process in the SDP mode should increase the anisotropy of the material being processed.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the publications [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ] studied the effect of dynamic action on several materials, which showed a significant effect of dynamic action on the structure, chemical composition, and properties of the processed materials. The authors of papers [ 33 , 34 , 35 , 36 , 37 ] investigated the effect of high-energy exposure combined with the impact on the target by a stream of high-speed particles.…”
Section: Introductionmentioning
confidence: 99%
“…The change in mechanical properties under dynamic alloying [35,[41][42][43] indirectly points to a change in the material's physical properties, and the peculiarities of the…”
Section: Table 4 the W6mo5cr4v2 Steel Hardnessmentioning
confidence: 99%
“…The recent experiments showed that when streams of cosmic dust particles collide with a spacecraft shield, it causes an occurrence of plasma, which in turn leads to the appearance of electromagnetic radiation capable of disabling nearby electrical equipment and superficial mechanical damage [1,6,7]. However, studies of dynamic alloying in the superdeep penetration (SDP) mode [2][3][4][5] also show that the collision of a high-speed cosmic dust streams should lead not only to electromagnetic radiation and superficial mechanical damage but also to penetration of cosmic dust particles into the spacecraft shell. Using dynamic alloying with high-speed streams of powder particles [10] will allow us to evaluate the effects that occur in the structure of material of the spacecraft.…”
Section: Introductionmentioning
confidence: 99%